Northern Shanghai Study II: systematic assessment and management of early organ damage and its role in preventing and reducing cardiovascular risk—protocol of a prospective study - Yi Zhang; Shikai Yu; Jun Han; Jingjing Hou; Moran Li; Xinming Jia; Fenyong Sun (BMJ Open)
Introduction Cardiovascular diseases are the leading cause of death and disease burden in China. However, there is a lack of prospective cohort studies suitable for evaluating early organ damage and its role in preventing and reducing cardiovascular risk among Chinese residents. This study intends to establish the first database based on the phenotypes of all early structural and functional damage of cardiovascular organs in Chinese population. Moreover, a digital follow-up mechanism will be formed, a prospective population cohort will be established, a biological sample bank for early cardiovascular organ damage will be established, and an intervention and management system for early damage of cardiovascular organs will be explored.Methods and analysis This study is a prospective cohort study built on the foundation of the Northern Shanghai Study I. People aged 18–75 years are enrolled. After the recruitment, first, corresponding physical measurements and clinical examinations are conducted to collect cardiovascular risk factors and establish the demographic baseline of the study population. Next, the latest equipment is used to evaluate early structural and functional cardiovascular organ damage including heart, macrovessels, microcirculation, renal function and fundus. Meanwhile, the blood, urine, faeces and other biological samples of participants are collected to establish the cardiometabolic and gut microbiota analysis databases. The population is followed up every 2 years. Comprehensive assessment of early organ damage will be used to predict cardiovascular risk, guide people to change lifestyles to achieve early prevention and provide corresponding treatment recommendations.Ethics and dissemination This study was approved by the Shanghai Tenth People’s Hospital Institutional Review Board. All participants signed a written consent form. The results of this study will be disseminated in peer-reviewed journals. Ethics approval: SHYS-IEC-5.0/22k148/P01.Trial registration number NCT05435898.